RELASI MAKNA ANTONIMI DAN SINONIMI DALAM CERPEN ROBOHNYA SURAU KAMI KARYA A.A. NAVIS - Dora Hatika Pertiwi; Neneng Nurjanah (Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to determine the relationship between synonymy and antonym in the short story The Collapse of Our Surau. This study uses a qualitative descriptive method with a semantic approach. The theory used in this study is the theory of semantic meaning relations. The technique used is the technique of observing and noting. The data of this research is the short story book The Collapse of Our Surau by A.A. Navis. This research instrument is in the form of documentation from the short story book The Collapse of Our Surau. The results of this study explain that there are 30 types of synonymous and antonymic meaning relations. The 20 synonyms that have meaning relations include 3 free and bound morpheme synonyms, 7 word synonyms for words, 1 word synonym for phrases, 4 phrase synonyms for phrases, and 5 word synonyms for clauses. The meaning of antonymy has 10 relations including 4 absolute antonymy relations, 1 relative antonymy or polar opposition, 1 directional antonymy, 3 relational antonyms, and 1 compound antonymy.